2023
DOI: 10.1063/5.0138171
|View full text |Cite
|
Sign up to set email alerts
|

Flexible metamaterial based microwave absorber with epoxy/graphene nanoplatelets composite as substrate

Abstract: Customization of substrates for the design of metamaterial absorbers gives the user a wide choice of parameters like flexibility, thickness, dielectric constant, etc. Polymer composites are attractive in this regard as they provide a variety of options to fabricate substrates with desirable properties depending on the matrix and filler materials. In this work, flexible polymer nanocomposites with different weight percentages of graphene nanoplatelets (GnP) in epoxy were fabricated and the dielectric characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Calculate the performance of the reflection loss (RL) of the coating using equivalent circuit theory based on its complex permittivity. 38,39 During the calculation process, the period C is equal to 10 mm, the size b is equal to 6 mm, the sheet resistance R is equal to 120 ohm, and the thickness t is equal to 2 mm. According to transmission line theory, when an electromagnetic wave is vertically incident on an absorber of this study, the reflectivity of the absorber can be represented by equivalent circuit shown in Figure 2.…”
Section: Experiments and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculate the performance of the reflection loss (RL) of the coating using equivalent circuit theory based on its complex permittivity. 38,39 During the calculation process, the period C is equal to 10 mm, the size b is equal to 6 mm, the sheet resistance R is equal to 120 ohm, and the thickness t is equal to 2 mm. According to transmission line theory, when an electromagnetic wave is vertically incident on an absorber of this study, the reflectivity of the absorber can be represented by equivalent circuit shown in Figure 2.…”
Section: Experiments and Designmentioning
confidence: 99%
“…The test frequency is between 8.2 and 18.0 GHz for radar waves. Calculate the performance of the reflection loss (RL) of the coating using equivalent circuit theory based on its complex permittivity 38,39 . During the calculation process, the period C is equal to 10 mm, the size b is equal to 6 mm, the sheet resistance R is equal to 120 ohm, and the thickness t is equal to 2 mm.…”
Section: Experiments and Designmentioning
confidence: 99%